1999
DOI: 10.1074/jbc.274.7.4089
|View full text |Cite
|
Sign up to set email alerts
|

The Calcium-binding Sites of Heparinase I fromFlavobacterium heparinum Are Essential for Enzymatic Activity

Abstract: , and Glu 381 in CB-2) that are important for calcium binding and heparinase I enzymatic activity. Mutations in CB-1 resulted in a lower k cat , but did not change the product profile of heparinase I action on heparin; conversely, mutations in CB-2 not only altered the k cat for heparinase I, but also resulted in incomplete degradation, leading to longer saccharides. Fluorescence competition experiments along with heparin affinity chromatography suggested that mutations in CB-1 alter heparinase I activity prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…Furthermore, through a combination of chemical modification and peptide mapping studies, we identify two calciumcoordinating motifs, with either one or both of these sites being important for the critical calcium-heparinase I interaction. In the accompanying study (14), we use the information derived herein to design a series of site-directed mutants of the calcium-binding sites of heparinase I to identify particular amino acids involved in calcium binding and critical for proper enzymatic functioning.…”
mentioning
confidence: 99%
“…Furthermore, through a combination of chemical modification and peptide mapping studies, we identify two calciumcoordinating motifs, with either one or both of these sites being important for the critical calcium-heparinase I interaction. In the accompanying study (14), we use the information derived herein to design a series of site-directed mutants of the calcium-binding sites of heparinase I to identify particular amino acids involved in calcium binding and critical for proper enzymatic functioning.…”
mentioning
confidence: 99%
“…The binding of Ca 2+ to alginate has been well documented (18,22), so it is possible that the true substrate for the epimerase reaction is the Ca 2+ -alginate complex. Finally, Ca 2+ is known to be a tightly bound cofactor in some enzymes (23,24). We therefore explored the Ca 2+ -dependence of the C5-mannuronan epimerase reaction.…”
Section: Discussionmentioning
confidence: 99%
“…12) Recent experiments on site-directed mutagenesis have found that the calcium-binding sequences of heparinase I are essential for the enzyme activity. 27,28) In r-heparinase expression, the addition of 1 mM IPTG caused the formation of an inclusion body, an inactive form that is precipitated by centrifugation. Therefore, the induction was done by a low concentration of 0.05 mM IPTG, which induced a soluble active form of r-heparinase without formation of an inclusion body, but the expression level was lower than expected.…”
Section: Discussionmentioning
confidence: 99%